2007
DOI: 10.1111/j.1743-8594.2007.00039.x
|View full text |Cite
|
Sign up to set email alerts
|

The Iraq War and Agenda Setting

Abstract: This essay takes concepts from early examples of a literature that is seldom used in foreign policy analysisFthe literature on agenda setting in the U.S. governmentFand applies it to the case study of the U.S. decision to launch Operation Iraqi Freedom in 2003. After a brief case history, the essay examines various core themes in the agenda-setting framework, and finds that concepts such as policy communities, focusing events, and policy windows can help explain the U.S. decision to go to war. The purpose of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 29 publications
0
30
0
5
Order By: Relevance
“…In Kingdon's analysis, policy advocates are akin to political entrepreneurs waiting for the alignment of circumstances that allows them to push their agenda to the fore. A powerful contemporary example is the initiation of Operation Iraqi Freedom (OIF) (Mazarr, 2007 This agenda became highly salient with the tragic events of 9/11, when the administration, under the context of a 'broader war on terror' (Mazarr, 2007: 6), immediately began the development of military plans. The important point here is not whether the military plans were wise or not, or what the exact motivations of the policy advocates were-the key issue (as relates to our arguments) is that these longstanding proposed actions would not have become policy in the absence of the events of 9/11.…”
Section: Option 2: Retrofi Tmentioning
confidence: 99%
“…In Kingdon's analysis, policy advocates are akin to political entrepreneurs waiting for the alignment of circumstances that allows them to push their agenda to the fore. A powerful contemporary example is the initiation of Operation Iraqi Freedom (OIF) (Mazarr, 2007 This agenda became highly salient with the tragic events of 9/11, when the administration, under the context of a 'broader war on terror' (Mazarr, 2007: 6), immediately began the development of military plans. The important point here is not whether the military plans were wise or not, or what the exact motivations of the policy advocates were-the key issue (as relates to our arguments) is that these longstanding proposed actions would not have become policy in the absence of the events of 9/11.…”
Section: Option 2: Retrofi Tmentioning
confidence: 99%
“…One definition is offered by Kingdon (, 21): “[a]n actor who advocates and seeks to change policy by exploiting opportunities and employing entrepreneurial strategies.” Mintrom (, 36), writing from a public policy perspective, adds, “[t]hey are individuals who through their creativity, strategy, networking, and persuasive argumentation are able to bring new policy ideas into the open and promote policy change.” Another definition is provided by Mazarr (, 16) who, writing from a constructivist perspective, states that “[p]olicy entrepreneurs can be seen as the human embodiment of the social construction of policy… . Advocates determined, for one reason or another, to fight inertia, the bureaucracy, opposing interests, and anything else in their way to get the idea through the window [of opportunity] and into law or policy.” These three definitions complement each other and are useful for this research.…”
Section: Policy Entrepreneurs and Us Foreign Policymentioning
confidence: 99%
“…Agenda-setting served as the guiding conceptual framework in this study. Studies have shown once issues like water are placed on the agenda (i.e., media agenda) and awareness of issues increases, the more likely individuals are to take action and reflect similar views on the issue (Lambright et al, 2006;Mazarr, 2007;Shiffman, 2007). A more active role from governmental and influential proponents driving the media agenda and public agenda have the ability to increase local and national awareness, further emphasizing the need for communicators to deliver this information to policy makers.…”
Section: Recommendations Practicementioning
confidence: 99%